Some Practical Aspects of the Relational Database Normalization Process - Pornphol, Putsadee; Chittayasothorn, Suphamit (My University, 2025)
Database normalization is a ubiquitous theoretical relational database analysis process. It comprises several levels of normal forms and encourage database designers not to split database tables into smaller ones unless it is necessary. Nevertheless, there are many aspects of relational database normalization which are not very well applied or well understood in practice. One of the biggest misconceptions is the misunderstanding that database normalization encourages splitting tables until they can be no longer spilt. Other popular practical misconceptions include over normalizations, performance issues, the complexity and rarity of multivalued and join dependencies, the projection/join normal form, and the unnecessity of carrying the normalization process beyond the third normal form or Boyce-Codd Normal Form (BCNF). This paper clarifies these practical misconceptions with positive examples and argues that relational database normalization process is a very practical analysis and quality control process of relational database table structures.
Keywords: Attribute Analysis; Conceptual Modelling; Normalization; Over normalization; Relational Databases